The reception of early transformational grammar in Europe - Frederick J. Newmeyer (Cadernos de Linguística, 2021)
The early success in the United States of Chomsky’s book Syntactic Structures and the theory of transformational-generative grammar that it introduced raises the question of the reception of the theory in other countries. Looking at Europe, there is no overarching generalisation. In some countries (the UK, the Netherlands) the theory enjoyed a great success, in others a moderate success, at least for a time (France, Germany), and in other countries very little success (Italy, Spain). Nevertheless, there is widespread agreement that European contributions to the theory have been among the most important.